2023
DOI: 10.1177/1024907920958861
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cardiopulmonary resuscitation that applied synchronous 30 compressions–2 ventilations with that applied asynchronous 110/min compression–10/min ventilation: A mannequin study

Abstract: Background: CPR model of a resuscitation to be ventilated with a bag valve mask constitutes a discussion when evaluated with the current guidance. Objective: This study aims to compare the synchronous (30–2) ventilation–compression method with asynchronous 110/min compression–10/min ventilation in cardiac arrests where an advanced airway management is not applied and where ventilation is provided by a bag valve mask on a mannequin. Methods: This simulation trial was performed using two clinical cardiopulmonary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The current ventilation strategy recommended by AHA for cardiac arrests is synchronous compression-ventilation for patients without use of an advanced airway and asynchronous method with ventilation once every 6 s for those with an advanced airway. 3 In this issue of Hong Kong Journal of Emergency Medicine (HKJEM), Küçükceran et al 4 explored compression and ventilation effects when synchronous versus asynchronous compression-ventilation methods were performed without advanced airway in mannequin models. The authors found that the chest compression fraction (CCF) in the asynchronous scenario was higher than for the synchronous scenario, whereas ventilation volume was lower in the asynchronous scenario.…”
mentioning
confidence: 99%
“…The current ventilation strategy recommended by AHA for cardiac arrests is synchronous compression-ventilation for patients without use of an advanced airway and asynchronous method with ventilation once every 6 s for those with an advanced airway. 3 In this issue of Hong Kong Journal of Emergency Medicine (HKJEM), Küçükceran et al 4 explored compression and ventilation effects when synchronous versus asynchronous compression-ventilation methods were performed without advanced airway in mannequin models. The authors found that the chest compression fraction (CCF) in the asynchronous scenario was higher than for the synchronous scenario, whereas ventilation volume was lower in the asynchronous scenario.…”
mentioning
confidence: 99%